2018
DOI: 10.15625/2525-2518/55/1a/12377
|View full text |Cite
|
Sign up to set email alerts
|

Rhodosporidium sp. GROWTH IN MOLASSES MEDIUM AND EXTRACTION OF ITS ASTAXANTHIN BY USING HCl

Abstract: Astaxanthin is classified as a xanthophyll-carotenoid, which is red-orange colour and powerful antioxidant activity. In this study, astaxanthin was collected from Rhodosporidum sp. by pilot culture (10 liters). Molasses medium was investigated with urea ((NH 4 ) 2 CO), magnesium sulfate heptahydrate (MgSO 4 .7H 2 O) and potassium dihydrogen phosphate (KH 2 PO 4 ) at different concentrations. Astaxanthin was extracted by using chlorhydric acid (HCl) method.The highest dried yeast biomass was 8.3682 g/l culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A number of studies have been done to test the ability of the solvents to isolate natural microbial carotenoids [40]; [41] but the investigation on the carotenoid release by mixtures of solvents had become a low attention. [42] showed that when multiple solvents i.e. dimethyl sulfoxide, petroleum ether and acetone were used together to disrupt the cell wall of the yeast Rhodotorula glutinis and thus to release the cellular carotenoid pigments, the mixture demonstrated a synergistic effect on the extent of carotenoid recovery.…”
Section: Potential Pigment-producing Microbes: Success and New Sourcesmentioning
confidence: 99%
“…A number of studies have been done to test the ability of the solvents to isolate natural microbial carotenoids [40]; [41] but the investigation on the carotenoid release by mixtures of solvents had become a low attention. [42] showed that when multiple solvents i.e. dimethyl sulfoxide, petroleum ether and acetone were used together to disrupt the cell wall of the yeast Rhodotorula glutinis and thus to release the cellular carotenoid pigments, the mixture demonstrated a synergistic effect on the extent of carotenoid recovery.…”
Section: Potential Pigment-producing Microbes: Success and New Sourcesmentioning
confidence: 99%